Analisis Perbandingan Metode Dempster Shafer Dengan Metode Certainty Factor Untuk Mendiagnosa Penyakit Stroke - Ira Lina Kendayto Panjaitan; Erwin Panggabean; Sulindawaty Sulindawaty (STMIK Pelita NUsantara, 2018)
Stroke is one of the function of acute neurologic dysfunction caused by vascular disorders and occurs suddenly, if it continues and is not treated promptly can result in total paralysis and even death.Often difficult to obtain services and information because there is no expert stroke disease that can provide information on how to choose the right action for himself or a family member who is suffering from stroke is a problem that is often a constraint in the prevention of disease stroke is more developed. In this study the authors analyze the comparison of diagnosis result of Expert System of stroke by using the method of Dempster Shafer and Certainty Factor. In expert System application in one disease there are a number of evidences that will be used in uncertainty factor in decision makin for diagnosis of a disease.To address some of these evedences on the theory of Dempster Shafer uses a rule better known as Dempster’s Rules of Combination. Certainty Factor is a theory to accommodate the inexact reasoning of an expert proposed by Shortliffe and Bhucanan in 1975. This expert system program is based on a website using the PHP programing language and MySQL database. Keyword : Expert System, Dempster Shafer, Certainty Factor, PHP